Analysis of recurrence after resection of well-differentiated non-functioning pancreatic neuroendocrine tumors. Issue 24 (12th June 2020) - Tan, Qing-quan; Wang, Xing; Yang, Le; Chen, Yong-Hua; Tan, Chun-lu; Zhu, Xiao-mei; Ke, Neng-wen; Liu, Xu-Bao
Abstract : Abstract: Although pancreatic neuroendocrine tumors (PNETs) are generally considered to have a favorable overall prognosis after resection, disease recurrence has been observed. Few studies have specifically addressed recurrence after resection of PNETs, especially for non-functioning PNETs (NF-PNETs). The aim of our study is to analyze the recurrence of resected well-differentiated NF-PNETs. Patients who underwent surgical resection for grade 1 and 2 NF-PNETs without synchronous metastasis were identified for analysis. Patients were treated from January 2009 to December 2017 in our institution. Univariate and multivariate cox regression analysis were conducted to identify prognostic factors. Of the 88 patients, 46 were men (52%) and the mean age was 52 years. With a median follow-up of 49.1 months (range, 8–122 months), there were 12 recurrences (14%). Liver was the most common recurrence site (7/12, 58%). The 1-, 3-, and 5-year recurrence-free survival was 99%, 90%, and 88%, respectively. Univariate analysis identified that age >52 years, positive lymph nodes, tumor grade 2, and Ki67 index ≥5% were statistically significant. Multivariate analysis identified that Ki67 index ≥5% (hazard ratio [HR], 4.69; 95% confidence interval [CI], 1.36–16.75, P  = .015), positive lymph nodes (HR, 6.75; 95% CI, 1.73–24.43, P  = .006) were independently associated with recurrence. The 5-year disease-free survival rate was 53% (95% CI, 14.20–91.81%) for patients with Ki-67 ≥5% or (and) positive lymph nodes, while 95% (95% CI, 82.26–100%) for the patients without these 2 factors. Ki67 index and lymph node status are independently associated with recurrence after resection of well-differentiated NF-PNETs in this study.